Role of Single Photon Emission Computed Tomography in Epilepsy. (11th November 2010) - Jayalakshmi, Sita; Sudhakar, Pushpalatha; Panigrahi, Manas
Abstract : Molecular imaging with ictal single photon emission computed tomography (SPECT) is an established functional imaging modality for the presurgical evaluation of patients with refractory partial onset seizures. SPECT coregistered on to the MRI has greater sensitivity to identify the ictal onset zone. Ictal SPECT should always be interpreted in the context of other presurgical investigations. Ictal SPECT is sensitive method for the lateralization of TLE, but ictal SPECT is more sensitive when MRI is normal. Ictal SPECT and interictal PET are complementary to each other in lateralizing the side in patients with TLE and normal MRI. In extratemporal epilepsy, ictal SPECT will guide the placement of surface grid and depth electrodes.